A general method for the detection of large CAG repeat expansions by fluorescent PCR. Issue 12 (December 1996) - Warner, J P; Barron, L H; Goudie, D; Kelly, K; Dow, D; Fitzpatrick, D R; Brock, D J
Abstract : The expansion of a tandemly repeated trinucleotide sequence, CAG, is the mutational mechanism for several human genetic diseases. We present a generally applicable PCR amplification method using a fluorescently labelled locus specific primer flanking the CAG repeat together with paired primers amplifying from multiple priming sites within the CAG repeat. Triplet repeat primed PCR (TP PCR) gives a characteristic ladder on the fluorescence trace enabling the rapid identification of large pathogenetic CAG repeats that cannot be amplified using flanking primers. We used our method to test a cohort of 183 people from myotonic dystrophy families including unaffected subjects and spouses. Eighty five clinically affected subjects with expanded alleles on Southern blot analysis were all correctly identified by TP PCR. This method is applicable for any human diseases involving CAG repeat expansions.